Light Distance And Ranging (LIDAR) data of elevations from Quarantine Bay and Neptune Pass, Louisiana, United States of America - Alexander Kolker; Dallon Weathers; Swann Christy; Renfro Alisha (PANGAEA, 2025)
This dataset contains Light Detection and Ranging (LiDAR) elevation data from Quarantine Bay and Neptune Pass, located in southeastern Louisiana, USA, on the east side of the lower Mississippi River. Data were collected on 6 October 2022 and 28 March 2023 to investigate landform development and vegetation dynamics associated with the expansion of Neptune Pass, the largest new distributary of the Mississippi River. The study area spans from 29.397°N to 29.272°N latitude and from -89.521°W to -89.474°W longitude. Data acquisition was performed using a DJI Matrice 300 RTK drone platform equipped with a Zenmuse L1 gimbal payload, which integrates both a LiDAR scanner and a high-resolution RGB camera. Digital elevation models (DEMs) and visible light mosaics were produced from dense 3D point clouds using DJI Terra (https://enterprise.dji.com/dji-terra) and CloudCompare (https://github.com/CloudCompare/CloudCompare/releases/). Georeferencing was achieved using real-time kinematic (RTK) GPS ground control points in QGIS to align LiDAR pulses and imagery with real-world coordinates. The final products include high-resolution DEMs and RGB orthomosaics suitable for geomorphological and ecological analysis.